Substance Abuse in Pregnancy: Opioid substitution in a Northern Ireland Maternity Unit - Mawhinney, Sandra (The Ulster Medical Society, 2006)
An increase in illicit drug use in Northern Ireland may well have links to the resolution of political conflict, which started in the mid 1990s. Social issues, heretofore hidden, have emerged into the limelight and may be worsened by paramilitary involvement.1 Registered addicts in the four Health Board areas have shown an increase from 1997 with the greatest number resident within the Northern Board Area.2 As the prevalence of heroin use in Northern Ireland increased, the Department of Health and Social Services and Public Safety (DHSSPS) commissioned a report, to recommend the development of substitute prescribing services.3 A case series of pregnancies was reviewed, within the Northern Board Area, where the mother was taking opioid substitution therapy. This resulted in baseline data of outcome for both mother and baby specific to a Northern Ireland population. The different medications for opioid substitution are also assessed. This information will guide a co-ordinated approach that involves obstetrician, anaesthetist, psychiatrist, midwife and social worker to the care of these high-risk pregnancies. Eighteen pregnancies were identified in the study period. Sixteen of these had viable outcomes. One was a twin pregnancy. Outcome data was therefore available for 17 infants. Information was obtained regarding patients' social and demographic background, drug taking behaviour and substitution regimen. Antenatal and intrapartum care was assessed and infants were followed up to the time of hospital discharge.